The Stock Market Valuation of Research and Development Expenditures - Chan, Louis K. C.; Lakonishok, Josef; Sougiannis, Theodore (Journal of Finance, 2001)
ABSTRACT We examine whether stock prices fully value firms' intangible assets, specifically research and development (R&D). Under current U.S. accounting standards, financial statements do not report intangible assets and R&D spending is expensed. Nonetheless, the average historical stock returns of firms doing R&D matches the returns of firms without R&D. However, the market is apparently too pessimistic about beaten‐down R&D‐intensive technology stocks' prospects. Companies with high R&D to equity market value (which tend to have poor past returns) earn large excess returns. A similar relation exists between advertising and stock returns. R&D intensity is positively associated with return volatility.